Mitogen-activated protein kinase 6 negatively regulates secondary wall biosynthesis by modulating MYB46 protein stability in Arabidopsis thaliana. - Jong Hee Im; Jae-Heung Ko; Won-Chan Kim; Brent Crain; Daniel Keathley; Kyung-Hwan Han (PLoS Genetics)
The R2R3-MYB transcription factor MYB46 functions as a master switch for secondary cell wall biosynthesis, ensuring the exquisite expression of the secondary wall biosynthetic genes in the tissues where secondary walls are critical for growth and development. At the same time, suppression of its function is needed when/where formation of secondary walls is not desirable. Little is known about how this opposing control of secondary cell wall formation is achieved. We used both transient and transgenic expression of MYB46 and mitogen-activated protein kinase 6 (MPK6) to investigate the molecular mechanism of the post-translational regulation of MYB46. We show that MYB46 is phosphorylated by MPK6, leading to site specific phosphorylation-dependent degradation of MYB46 by the ubiquitin-mediated proteasome pathway. In addition, the MPK6-mediated MYB46 phosphorylation was found to regulate in planta secondary wall forming function of MYB46. Furthermore, we provide experimental evidences that MYB83, a paralog of MYB46, is not regulated by MPK6. The coupling of MPK signaling to MYB46 function provides insights into the tissue- and/or condition-specific activity of MYB46 for secondary wall biosynthesis.